The Effect of Teams Games Tournament (TGT) and Team Assisted Individualization (TAI) Learning Models on The Mains of Discussion Reviewed From Student's Learning Creativity - Iwan Kurnianto; Budi Usodo; Sri Subanti (Universitas Sebelas Maret, 2020)
This study aims to determine: which ones provide better Mathematics learning outcomes; which students have better Mathematics learning achievement, students with high, medium or low creativity; for each creativity level that gives better Mathematics learning outcomes; for each mathematics learning model that has better mathematics learning achievement in students of high, medium, or low creativity on Numbers material for learning TGT, TAI. This type of research is a quasi-experimental research with a 3 x 3 factorial design. The population in this study were all students of grade VII SMP in Kudus Regency 2015/2016 academic year. The research sample was taken using stratified cluster random sampling technique. The samples of this study were students of class VII SMP Negeri 1 Mejobo, SMP Negeri 1 Bae, and SMP Negeri 3 Bae. The results obtained, TGT provides better mathematics learning achievement than TAI. students with high and moderate creativity have the same mathematics learning achievement. students with TGT have better mathematics learning achievement than TAI students. students with high and moderate creativity have the same mathematics learning achievement.